Universal screening for familial hypercholesterolemia in children: The Slovenian model and literature review - Groselj, Urh; Kovac, Jernej; Sustar, Ursa; Mlinaric, Matej; Fras, Zlatko; Podkrajsek, Katarina Trebusak; Battelino, Tadej (Atherosclerosis, 2018)
Familial hypercholesterolemia (FH) is arguably the most common monogenic disorder in humans, but severely under-diagnosed. Individuals with untreated FH have an over 10-fold elevated risk of cardiovascular complications as compared to unaffected individuals; early diagnosis and timely management substantially reduce this risk. Slovenia has gradually implemented the program of universal FH screening in pre-school children, consisting of a two step approach: (1) universal hypercholesterolemia screening in pre-school children at the primary care level; (2) genetic FH screening in children referred to the tertiary care level according to clinical guidelines (with additional cascade screening of family members). The program is presented in detail. We analyzed retrospective data (2012–2016), to assess the efficiency of the universal FH screening program. In that period, 280 children (59.3% female) were referred to our center through the program for having TC > 6 mmol/L (231.7 mg/dL) or >5 mmol/L (193.1 mg/dL), with a positive family history of premature cardiovascular complications at the universal hypercholesterolemia screening. 170 (57.1% female) of them were fully genotyped, 44.7% had an FH disease-causing variant (28.8% in LDLR gene, 15.9% in APOB, none in PCSK9), one patient was LIPA positive, and 40.9% of the remaining patients carried an ApoE4 isoform; genetic analysis is still ongoing for one-third of the referred patients. For almost every child with confirmed FH, one parent had highly probable FH. FH was confirmed in almost half of the referred children, detected through the universal screening for hypercholesterolemia. •FH is a common monogenic disorder but severely under diagnosed and under treated.•FH screening in childhood with early treatment is needed.•Slovenia has a unique and effective program of universal FH screening in children.•Almost half of the children referred through the program had FH causing mutation.